Studi Analisa Motor Induksi Tiga Fasa dengan Sumber Tegangan Satu Fasa: Analysis Study of a Three-Phase Induction Motor with a Single-Phase Voltage Source - Arsel, Sandy Permana; Rauf, Rosnita; Budiman, Budiman (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Three-phase induction motors are generally operated using a three-phase power source. To overcome problems in a three-phase power system, a single-phase power source can be used to drive a three-phase induction motor. Operating a three-phase induction motor with a single-phase power source can be done by creating a circuit similar to that of a single-phase capacitor induction motor. The primary coils are known as the (V-Y) and (W-Z) coils, while the secondary coils are called the (U-X) coils. The purpose of this study is to understand the working principle of a three-phase induction motor, to be able to analyze the experimental results of induction motors connected to a three-phase source or connected to a single-phase source, and to compare the operation of a three-phase induction motor with a three-phase source or with a single-phase source. The study employed a quantitative research method, utilizing observational and descriptive data collection techniques. The research methodology is systematic and directed, following the flowchart diagram. The description of the equivalent circuit is the same as the equivalent circuit of a single-phase capacitor-running induction motor. So the equation used in the analysis is the equation of a capacitor-running induction motor. In this study, a three-phase induction motor with a 220/380 ?/Y Voltage, 4.7/2.7 Amperes, 50 Hz, and 1000 watts is used, featuring a cos ? value of 0.76. From the results of research conducted on a three-phase induction motor with a single-phase source at a load condition of 180 watts. The torque value is 0.88 N · m, the input current is 2.90 A, the input power is 421.08 W, cos ? is 0.66, and the resulting efficiency is 37%.